Analisis Faktor-Faktor Yang Mempengaruhi Kunjungan Wisatawan Ke Kota Batu - Haomoan Sihombing, Jeffry Daniel (Jurnal Ilmiah Mahasiswa FEB, 2016)
This  study  aimedto  determine  the  effectofpeople income,  travel  costs,  travel  time,  facilities,  andcity brandingtovisitingBatu City.  The  researchmethodsusequantitativemethodwith adescriptive approach. This  study usesprimary databy using aquestionnaireas a tool tocollectdata. Results of this study can be concluded that the reason tourists visit the Batu City are the travel time and facilities for tourism. People income variable and travel cost variable does not significantly affect to tourist visiting Batu City. While city branding influence significantly but have negative correlated to the tourists visiting Batu City.   Keyword: tourism demand, city branding, travel cost